The Influence of Online Customer Reviews on the Purchase Decision of Room Services at Turi Beach Resort Batam - Rahmat Riski; Nidia Wulansari (Journal of Multidimensional Management, 2025)
In the digital era, online customer reviews have become a critical factor influencing consumer behavior, particularly in the hospitality industry where service quality and trust are decisive. This study aims to analyze the influence of online customer reviews on purchase decisions for room services at Turi Beach Resort Batam, one of the leading resorts in Indonesia’s border tourism area. Employing a quantitative approach, data were collected from 100 guests who made reservations through online travel agents (OTAs) and digital platforms. The data were analyzed using regression analysis to test the significance of the relationship between online customer reviews and purchase decisions. The results indicate that online customer reviews have a strong and significant positive effect on the purchase decision of room services, with an R² value of 0.646 and a p-value < 0.001. These findings highlight that potential customers perceive online reviews as a reliable source of information that reduces uncertainty and enhances confidence in their booking decisions. The study underscores the importance for hospitality managers to actively monitor, manage, and respond to online reviews as part of their digital marketing and reputation management strategies. This research contributes to the growing literature on electronic word-of-mouth (e-WOM) and consumer decision-making in the hospitality sector, while also offering practical implications for resort operators seeking to strengthen competitiveness through digital engagement.